An Examination of Central Bank Independence and Power - Pandey, Ravindra Prasad (NRB Economic Review, 2005)
The argument which stresses the role of an independent central bank in preserving the soundness of money by ensuring a low rate of inflation tends to be both narrow and inconsistent. However, much of the debate for independent central banks derives from empirical evidence rather than from theoretical propositions, and if low rates of inflation could be clearly demonstrated to lead to higher rates of economic growth and/or more stable rates of growth, it would provide an argument with which it would be difficult to disagree with the proposition that the market economy operates more efficiently at low rates of inflation. As macroeconomic policy has been developing at a fast pace in recent years, governments have increasingly moved in the direction of restricting themselves to the use of one instrument of policy. It is in this context that the role of the central bank has been accorded so much focus along with its governance. At the same time, there has been a significant move to increase the independence and power of central banks. This would appear to be placing macroeconomic policy almost entirely in the hands of central banks. Yet, monetary policy seems only likely to be effective when central banks behave in the way that financial markets expect and wish them to do so. Moreover, governments seem to have little control over the operation of financial markets. This appears to remove macroeconomic policy entirely not just from short-sighted politicians but from any institutions which might be expected to have the best interests of the entire economy at heart.